Several audiotapes with speeches by Hitler, Rudel and during neonazist meetings in the Löwenbräukeller in München - Hitler, Adolf.
Several audiotapes with speeches by Hitler, Rudel and during neonazist meetings in the Löwenbräukeller in München.